Performance evaluation of non-ionic silicone surfactants OFX 0309 and DC 193C as a new approach in cloud point extraction – spectrophotometry for determination of atrazine in water samples - Mohd, Noraini; Raoov, Muggundha; Mohamad, Sharifah; Zain, Nur Nadhirah Mohamad (Royal Society of Chemistry, 2018)
Cloud point extraction (CPE)-spectrophotometric method had been adopted for the separation of atrazine using the non-ionic silicone surfactant, polysiloxane polyether, as a new approach of atrazine extractor in CPE. There were two types of polysiloxane polyether (DC 193C and OFX 0309) studied to investigate the effectiveness of these surfactants toward atrazine in CPE method. Various effects of operating parameters such as the concentration of surfactant and atrazine, addition of salt and change of temperature and pH on the extraction of atrazine have been studied in detail to find the optimum conditions. The limit of detections (LODs) and quantifications (LOQs) were in the range of 0.09-0.59 μg L-1 and 0.31-1.95 μg L-1 in water samples, respectively. The method recoveries at two spiked levels were 84-105% (CPE-OFX 0309) and 59-69% (CPE-DC 193C) with good correlation of determination (R2) ranging from 0.9927-0.9993 for both methods. The Langmuir isotherm has been used for solubilisation study of surfactant and atrazine. The thermodynamic parameters have been determined such as Gibbs free energy (ΔG°) which increases with temperature, value of enthalpy (ΔH°) and value of entropy (ΔS°) which increase with the surfactant hydrophobicity.